Impact of septic episodes caused by Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa in a tertiary hospital: clinical and economic considerations in years 2018–2020. Issue 4 (April 2023) - Garlasco, Jacopo; Beqiraj, Iva; Bolla, Cesare; Marino, Elisabeth Maria Irene; Zanelli, Cristian; Gualco, Corrado; Rocchetti, Andrea; Gianino, Maria Michela
Abstract: Objective: To evaluate incidence, therapy and antibiotic resistance trends in septic episodes caused by three multi-drug resistant bacteria in a tertiary hospital, by also estimating their economic impact. Methods: An observational, retrospective-cohort analysis was based on data related to patients admitted to the "SS. Antonio e Biagio e Cesare Arrigo" Hospital in Alessandria (Italy) between 2018 and 2020, that developed sepsis from multi-drug resistant bacteria of the examined species. Data were retrieved from medical records and from the hospital's management department. Results: Inclusion criteria led to enrolment of 174 patients. A relative increase in A. baumannii cases ( p < 0.0001) and an increasing resistance trend for K. pneumoniae ( p < 0.0001) were detected in 2020 compared to 2018–2019. Most patients were treated with carbapenems (72.4%), although the use of colistin rose significantly in 2020 (62.5% vs 36%, p = 0.0005). Altogether, these 174 cases caused 3295 additional hospitalisation days (mean 19 days/patient): the consequent expenditure attained ≈ 3 million Euros, 85% of which (≈2.5 million Euros) due to the cost of extra hospital stay. Specific antimicrobial therapy accounted for 11.2% of the total (≈336, 000 €). Conclusions: Healthcare-related septic episodes cause a considerable burden. Moreover, a trend could be spotted towards higher relative incidence of complex cases recently.